Job Satisfaction as a Mediator between Work Culture, Compensation, and Employee Performance at Sanak Retreat Bali - Wirayuni, Kadek Wiwik; Telagawahi, Ni Luh Wayan Sayang; Hervanda, Komang Krisna (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to examine the influence of work culture and compensation on employee performance, with job satisfaction acting as a mediating variable at Sanak Retreat Bali, a hospitality and tourism company located in Bali. Work culture and compensation are key factors believed to enhance employee motivation and satisfaction, which in turn positively impact performance. A quantitative approach was employed using a survey method, involving employees of Sanak Retreat Bali selected through purposive sampling. Data were collected via questionnaires and analyzed using Structural Equation Modeling (SEM). The results reveal that both work culture and compensation significantly affect job satisfaction, and that job satisfaction mediates the relationship between these factors and employee performance. These findings highlight the importance of fostering a positive work culture and implementing a fair compensation system to improve both employee satisfaction and performance in the tourism sector. Therefore, it is recommended that the management of Sanak Retreat Bali continue to enhance its organizational culture and compensation strategies to support employee productivity and loyalty.